Genome-wide analysis of the TCP gene family and their expression pattern in Cymbidium goeringii - Liu, Ding-Kun; Zhang, Cuili; Zhao, Xuewei; Ke, Shijie; Li, Yuanyuan; Zhang, Diyang; Zheng, Qinyao; Li, Ming-He; Lan, Siren; Liu, Zhong-Jian (Frontiers in Plant Science, 2022)
TCP gene family are specific transcription factors for plant, and considered to play an important role in development and growth. However, few related studies investigated the TCP gene trait and how it plays a role in growth and development of Orchidaceae. In this study, we obtained 14 TCP genes (CgTCPs) from the Spring Orchid Cymbidium goeringii genome. The classification results showed that 14 CgTCPs were mainly divided into two clades as follows: four PCF genes (Class I), nine CIN genes and one CYC gene (Class II). The sequence analysis showed that the TCP proteins of C. goeringii contain four conserved regions (basic Helix-Loop-Helix) in the TCP domain. The exon−intron structure varied in the clade according to a comparative investigation of the gene structure, and some genes had no introns. There are fewer CgTCP homologous gene pairs compared with Dendrobium catenatum and Phalaenopsis equestris, suggesting that the TCP genes in C. goeringii suffered more loss events. The majority of the cis-elements revealed to be enriched in the function of light responsiveness, followed by MeJA and ABA responsiveness, demonstrating their functions in regulating by light and phytohormones. The collinearity study revealed that the TCPs in D. catenatum, P. equestris and C. goeringii almost 1:1. The transcriptomic data and real-time reverse transcription-quantitative PCR (RT−qPCR) expression profiles showed that the flower-specific expression of the TCP class II genes (CgCIN2, CgCIN5 and CgCIN6) may be related to the regulation of florescence. Altogether, this study provides a comprehensive analysis uncovering the underlying function of TCP genes in Orchidaceae.